THE EFFECT OF SOLVENCY AND LIQUIDITY ON THE PROFITABILITY OF INDONESIAN AND SAUDI ARABIAN ISLAMIC COMMERCIAL BANKS: AN EMPIRICAL ANALYSIS BASED ON STAKEHOLDER THEORY - Puspitasari, Kartika; Muflih, Muhammad (Accounting Department, Politeknik Negeri Bandung, 2024)
Profitability in Islamic banking is currently less competitive compared to conventional banking, including in Indonesia and Saudi Arabia. This study aims to enhance the profitability of Islamic banking in Indonesia and Saudi Arabia during the period 2013–2022 by examining the role of solvency (DER), liquidity (CR), and company size (SIZE) as control variables based on stakeholder theory. The data for this study were derived from Islamic banking financial reports collected through purposive sampling and analyzed using SEM-PLS techniques. The study found that solvency and company size, as control variables, have a significant impact on the profitability of Islamic commercial banks in Indonesia and Saudi Arabia. However, liquidity in Islamic banking in both countries does not significantly affect profitability. These findings provide guidance for Islamic banking institutions in formulating strategic initiatives to enhance the profitability of Islamic commercial banks in Muslim-majority countries.